Afatinib maintenance therapy following post-operative radiochemotherapy in head and neck squamous cell carcinoma: Results from the phase III randomised double-blind placebo-controlled study BIB2992ORL (GORTEC 2010–02). (January 2023) - Racadot, Séverine; Thennevet, Isabelle; Ouldbey, Yaelle; Kaminsky, Marie-Christine; Bosset, Mathieu; Martin, Laurent; Tao, Yungan; Sire, Christian; de Raucourt, Dominique; Alfonsi, Marc; Malaurie, Emmanuelle; Tourani, Jean-Marc; et al.
Abstract: Objective: We investigated the efficacy and safety of afatinib maintenance therapy in patients with head and neck squamous cell carcinoma (HNSCC) with macroscopically complete resection and adjuvant radiochemotherapy (RCT). Methods: This French multicentric randomised phase III double-blind placebo-controlled study included adult patients with ECOG-PS≤2, normal haematological, hepatic and renal functions, and non-metastatic, histologically confirmed HNSCC of the oral cavity, oropharynx, larynx or hypopharynx, with macroscopically complete resection and adjuvant RCT (≥2 cycles of cisplatin 100 mg/m2 J1, J22, J43 and 66Gy (2Gy/fraction, 5 fractions/week, conventional or intensity modulated radiotherapy ≥60Gy). Randomised patients were planned to receive either afatinib (afa arm) or placebo (control arm (C)) as maintenance therapy for one year. Primary endpoint was disease free survival (DFS). A 15% improvement in DFS was expected at 2 years with afatinib (from 55 to 70%). Results: Among the 167 patients with resected HNSCC included in 19 cancer centres and hospitals from Dec 2011, 134 patients were randomised to receive one-year maintenance afatinib or placebo (afa:67; C:67). Benefit/risk ratio was below assumptions and independent advisory committee recommended to stop the study in Feb 2017, the sponsor decided premature study discontinuation, with a 2-year follow-up for the last randomised patient. 2y-DFS was 61% (95% CI 0.48–0.72) in the afatinib group and 64% (95% CI 0.51–0.74) in the placebo group (HR 1.12, 95% CI 0.70–1.80). Conclusion: Maintenance therapy with afatinib compared with placebo following post-operative RCT in patients with HNSCC did not significantly improve 2y-DFS and should not be recommended in this setting outside clinical trials. ClinicalTrials.gov identifier NCT01427478. Highlights: The study planned one-year afatinib maintenance therapy (N = 67) or placebo (N = 67). Afatinib after post-operative RCT showed no improved 2y-DFS in patients with HNSCC. Afatinib should not be recommended in this setting outside clinical trials.